Targeting the hallmarks of cancer: the effects of silibinin on proliferation, cell death, angiogenesis, and migration in colorectal cancer - Saba Sameri; Chiman Mohammadi; Mehrnaz Mehrabani; Rezvan Najafi (BMC, 2021)
Abstract Background Silibinin, as a chemopreventive agent, has shown anti-cancer efficacy against different types of cancers. In the present study, we investigated the anti-cancer activities of silibinin on CT26 mouse colon cell line. Methods CT26 cells were treated with different concentrations of silibinin. To examine the cytotoxic effect of silibinin on proliferation, apoptosis, autophagy, angiogenesis, and migration, MTT, colony-forming assay, Annexin V/PI flow cytometry, RT-qPCR, and Scratch assay were used. Results Silibinin was found to significantly reduce CT26 cells survival. Furthermore, silibinin strongly induced apoptosis and autophagy by up-regulating the expression of Bax, Caspase-3, Atg5, Atg7 and BECN1 and down-regulating Bcl-2. Silibinin considerably down-regulated the expression of COX-2, HIF-1α, VEGF, Ang-2, and Ang-4 as well as the expression of MMP-2, MMP-9, CCR-2 and CXCR-4. Conclusions The present study revealed that silibinin shows anticancer activities by targeting proliferation, cell survival, angiogenesis, and migration of CT26 cells.